Sustainable green pretreatment approach to biomass-to-energy conversion using natural hydro-low-transition-temperature mixtures - Yiin, C.L. (Elsevier Ltd, 2018)
Natural hydro-low-transition-temperature mixtures (NH-LTTMs) tend to be the most favorable next-generation green solvents for biomass pretreatment, as they are cheap and environmental friendly. The amount of water bound into the NH-LTTMs greatly affected their thermal stability, whereby the highest thermal stability was observed with the water content of 7.6 wt. It is worth noting that, the highest molar transition energy of NH-LTTMs (47.57 kcal molâ1), which indicated the highest solubility, was optimized with the molar ratio of hydrogen bond donor (HBD)-hydrogen bond acceptor (HBA)-water (2:4:3) at a temperature of 60 Â°C. Hydrogen bonding networks of the NH-LTTMs, which led to the dissolution of biomass, were confirmed by the alteration in the peaks of the involved bonds and resonance signal to lower field through FTIR and 1H NMR spectra, respectively. The components evidenced in high-resolution mass spectra of extracted lignin showed its high potential to be valorized into useful fuels and chemicals. Â© 2018 Elsevier Ltd